KEDUDUKAN ANAK ADOPSI DALAM PEMBAGIAN HARTA WARISAN MILIK ORANG TUA ADOPSINYA - ahmad basthomi (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACT Adoption carried out by people with the motivation and the reasons vary , according to the legal system that live and thrive in their respective areas . Adopted in customary law is other people's children raised by adoptive parents with the authorized according to customary law, because the purpose for offspring survival or maintenance of household wealth . Special in East Borneo works raised this child will eventually arise familial relationship between the adoptive parents with children who are raised . While Islamic law does not recognize adopted children but does not deny the existence of child welfare and foster so far provide for the child . According to Islamic law a child may not receive the entire inheritance from his adoptive parents , or if there is no probate law , an adopted child will not receive the slightest legacy of his adoptive parents .